Cultural validation of the diabetic family behavior checklist among Filipino, diabetic patients and their family members - Ereso-De Mesa, Mary Jane V.
By the year 2030, the number of diabetic patient is expected to triple reaching around 8,000,000 population world-wide. Research on families and health demonstrates the powerful influence and benefits of family intervention illness like diabetes. This supports the importance of family-oriented approach to clinical practice. At present there is no locally validated and reliable tool that could assess the supportive and non-supportive behaviors specific of Filipino diabetic patients. The general objectives of this study is to determine the validity and reliability of a Filipino version Diabetic Family Behavior Checklist that is culturally appropriate for use among ambulatory Type 2 diabetic patients and their family members. The general objectives of this study is to determine the validity and reliability of a Filipino version Diabetic Family Behavior Checklist that is culturally appropriate for use among ambulatory Type 2 diabetic patients and their family members. This study utilized a two-phase cross sectional design. The first included two-step procedure namely protocol translation and cultural adaptation of the questionnaire. The second phase was the psychometric testing through determination of the validity, reliability and hypothesis testing of the translated Diabetic Family Behavior Checklist instrument. Non probability sampling was done from Canossa Health and Social Center, UP-PGH out-patient clinics of family medicine and internal medicine-DM Clinic and UP-FMAB Out-patient clinics of family medicine and Internal medicine-endocrine clinic. To questionnaire had undergone cross-cultural translation having conceptual equivalence, item equivalence, semantic equivalence, operational equivalence, and measurement equivalence. Convergent validity of the tool using Spearman's rho test that the answers of the diabetic patient and their family members in all 16 items has moderate positive association (p<0.01 or p-<0.05). Construct validity was appropriate based from factor analysis result of Kaiser Meyer Olkin Measure of Sampling Adequacy (KMO=0.867, p=0.000) and Goodness of fit test (X2(189), df 89, p=0.000). Reliability analysis showed Cronbach's alpha value of 0.8795 which showed a high level of internal consistency for the Tagalog-version of the DFBC scale. First hypothesis that overall, age was not a factor in receiving supportive and non-supportive care from the family members of diabetic patients. Of the 16 items only item #8 "Himukin ka na sumali sa mga gawaing pampalakasan o "sports" (phi=0.312, P=0.001) and item #9 "Magplano ng mga gawaing pampamilya na tumutugma sa iskedyul ng iyong sariling pangangalaga kontra diabetes" (phi=0.726, p=0.002) has a strong and positive relationship with regards to age. Second hypothesis revealed that control of sugar as measured by hemoglobin A1c levels was not associated with their supportive or non-supportive behaviors received from family members. Only item #7 "Makipagdiskusyon tungkol sa inyong sariling pangangalaga kontra diabetes" of the non-supportive behavior was positively related to the level of hemoglobin A1c (phi=0.224, p=0.014). Third hypothesis showed that overall diabetic patients from functional family as measured by Filipino Family APGAR have received more supportive care from their family members (p=0.01). The supportive behavior item 313 "Nage-ehersisyo na kasabay mo" was the only supportive feedback with strong, positive relationship with APGAR score (phi=0.268, p=0.005).
Thesis--(Master of Science in Clinical Medicine-Family Medicine)--University of the Philippines Manila
Keywords: Diabetics -- Family relationships